About two seal‐impressed jars from Tell Abraq (Emirate of Umm al‐Quwain). New evidence for intercultural networks in the lower Arabian Gulf in the late 2nd – beginning of the 1st millennium BC. (31st July 2022) - Majchrzak, Dominika; Esposti, Michele Degli
Abstract: Ongoing excavations at Tell Abraq (Emirate of Umm al‐Quwain, U.A.E.) are revealing new aspects of this multiperiod site, which was occupied from c. 2500 BC to 300 AD. Together with substantial architecture dated to the 2nd and 1st millennia BC, relevant assemblages of archaeological materials are being collected and dated to different phases of the site's life. Among this material, exceptional is the discovery of two jars bearing the impression of two different cylinder seals, which will be presented here. Seal impressions on any media are extremely rare in the whole of south‐eastern Arabia and strongly indicate a foreign provenance for the jars. Their iconographic study, the fabric and morphological parallels for the jars, and probable chronology will be discussed, as this can highlight transmarine connections during the late 2nd‐first half of the 1st millennium BC, as well as provide new data to address chronological issues in south‐eastern Iran itself.